ANALISIS DEWAN DIREKSI, DEWAN KOMISARIS DAN KOMITE AUDIT TERHADAP KINERJA KEUANGAN DI BANK KONVENSIONAL - Hakim, Moh Irman; Gideon Setyo Budiwitjaksono (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2023)
The purpose of this study is to ascertain and evaluate the impact of the board of directors, board of commissioners, and audit committee on financial performance a proxy the return on assets (ROA) in conventional bank listed on the Indonesia Stock Exchange for the years 2018 through 2021. The methodology utilized in this study is quantitative one, and it makes use of secondary data in the form of traditional bank yearly financial reports that were collected from the Indonesia Stock Exchange’s official website (www.idx.co.id). Purposive sampling was the method utilized to choose the sample for this study, and it took 4 years to collect 108 samples. According to the study’s findings, the board of directors significantly affects financial performance. However, the board of commissioners and audit committee do not significantly affect the financial performance of traditional banks from 2018 to 2021. This study offers suggestions and additional proof regarding the impact of the board of directors, board of commissioners, and audit committee on the financial performance, particularly the banking sector.